The forces that divide: understanding tension and unity among provincial correctional workers in Canada - McKendy, Laura (Criminal justice studies, 2022)
Recognizing the importance of occupational social climates in shaping correctional work, we consider how social relations of work are understood by provincial correctional workers, including how organizational and operational factors influence such relations. Open-ended survey responses with provincial correctional workers in the provinces of Saskatchewan and Manitoba were thematically analyzed to explore perceptions of unity and tension within the occupational social terrain. We found a notable disconnect between frontline staff and senior management, marked by a bottom-up sense of mistrust and frustration. Contrary to findings elsewhere, a sense of outward suspicion did not appear to occur in parallel to a strong inward solidarity. Horizontal social relations were often described as fragmented due to factors such as divisive social practices (e.g. gossiping, cliques), normative occupational ideals, labor and work structures that create status differences and fluid work environments, and trying conditions of work. In this context, individualist rather than collectivist dispositions can come to shape working orientations, thus representing a contrast from traditional elements of frontline correctional cultures, such as in-group solidarity and loyalty.